2019
DOI: 10.1111/iwj.13115
|View full text |Cite
|
Sign up to set email alerts
|

Leg ulcer induced by hydroxycarbamide in sickle cell disease: What is the therapeutic impact?

Abstract: Major sickle cell disease syndrome (SCD) is a set of potentially serious and disabling constitutional haemoglobin pathologies characterised by chronic haemolysis and vaso‐occlusion phenomena. If expression takes the form of acute vaso‐occlusive crisis, SCD is currently considered to be a chronic systemic pathology, primarily associated with vasculopathy and ischaemia‐reperfusion phenomena. The haemolytic aspect of the disease may be associated with endothelial dysfunctional complications, including leg ulcers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…7 This may also imply that therapeutic interventions targeted against leucocytes (including expression of their adhesion molecules) may not successfully reduce the prevalence of this complication, as has been reported with hydroxycarbamide. 24 However, variations in absolute numbers may not represent consequent variations in function or degree of expression of surface molecules as had been noted in SCA.…”
Section: Discussionmentioning
confidence: 99%
“…7 This may also imply that therapeutic interventions targeted against leucocytes (including expression of their adhesion molecules) may not successfully reduce the prevalence of this complication, as has been reported with hydroxycarbamide. 24 However, variations in absolute numbers may not represent consequent variations in function or degree of expression of surface molecules as had been noted in SCA.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62][63] Soya et al reported a case of an SCD patient who developed a leg ulcer 18 days after the introduction of HU and healed after HU was stopped. 64 The authors proposed that the accumulation of HU under the skin could have caused cutaneous atrophy and impaired microcirculation. 64 An alternate hypothesis could be that the level of HbF reached during HU treatment was not enough to provide clinical benefits.…”
Section: Haemolysismentioning
confidence: 99%
“…31 The lesions associated with HC are most often malleolar and have a fibrotic appearance, with inflammatory margins but without necrosis. 32…”
Section: Pathophysiologymentioning
confidence: 99%
“…Hydroxycarbamide can alter microcirculation and cause anoxia of the tissue, which explains the incidence of skin ulcers following minimal trauma and their sometimes painful nature 31 . The lesions associated with HC are most often malleolar and have a fibrotic appearance, with inflammatory margins but without necrosis 32 …”
Section: Pathophysiologymentioning
confidence: 99%